Correction to: Experimental Study on Seismic Capacity of Reinforced Concrete Composite Columns Based on a High-ductile Fiber Cementitious Composite - Chang-Geun Cho; Sang-Hyeon Cheong; Hyung-Ju Moon; Ho-Yeon Kim; Kang-Seok Lee (International Journal of Concrete Structures and Materials, 2019)
Following publication of the original article (Cho et al. 2019), the author reported the funding source information must be replaced with following: This research was supported by the National Research Foundation of Korea Grant funded by the Ministry of Education, Korea (No. 2018R1A2B2003258), and National Research Foundation of Korea Grant 017R1A2B4008983, funded by the Ministry of Education, Korea.